2011
DOI: 10.1080/09593330.2010.517218
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of soils contaminated with chromium using citric and hydrochloric acids: the role of chromium fractionation in chromium leaching

Abstract: Acid washing is a common method for soil remediation, but is not always efficient for chromium-contaminated soil. Both soil particle size and the forms of chromium existing in the soil affect the efficiency of soil washing. Laboratory batch and column dissolution experiments were conducted to determine the efficiencies of citric and hydrochloric acids as agents to extract chromium from soils contaminated with chromium. The effects of soil particle size and chromium fractionation on Cr leaching were also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…B9. The inhibition of Cr(VI) removal by some heavy metals at elevated concentrations maybe due to the suppression of microbial activity by metal toxicity, and the destruction of protein structures by heavy metals [14].…”
Section: Effects Of Coexisting Heavy Metals On Cr(vi) Reductionmentioning
confidence: 99%
“…B9. The inhibition of Cr(VI) removal by some heavy metals at elevated concentrations maybe due to the suppression of microbial activity by metal toxicity, and the destruction of protein structures by heavy metals [14].…”
Section: Effects Of Coexisting Heavy Metals On Cr(vi) Reductionmentioning
confidence: 99%
“…In an oxic environment, Cr exists as Cr(VI), while in an anoxic environment Cr(VI) is readily reduced to Cr(III) by ferrous oxides and ferric oxyhydroxides as ferrihydrite (Fe 2 O 3 •0.5H 2 O), goethite (FeOOH) and hematite (Fe 2 O 3 ) due to their abundant occurrence and large surface area. Besides ferrous oxides, Cr(VI) can be naturally reduced to Cr(III) by various other reducing agents such as S 2ions, organic matter, and by microbial communities (Banks et al 2006;Cheng et al 2011). The oxidation of Cr in the soil can be caused by low molecular mass organic acids (citric acid, gallic acid, etc.)…”
mentioning
confidence: 99%
“…For surfactants, it has been reported that this type of agent has good potential for removing metals in soil. However, popular surfactants are the cationic, anionic and nonionic types that can be used for washing (Mulligan et al, 1999) such as TWEEN 80, Triton X-100, Brij-35 (nonionic surfactant), SDS, AOT, SDBS (anionic surfactant) and hydrochloric acids (Kos and Lestan, 2004;Cheng et al, 2011;Xuhui et al, 2015;Min et al, 2017). According to the findings in many studies, filling surfactants in contaminated soil could enhance the emission and dissolution of contaminated organic matter because the solvent as cooled water needs to have a low Critical Micelle Concentration (CMC) related to a low value of toxic microbes (Cheng and Wong, 2006).…”
Section: Introductionmentioning
confidence: 99%